2014
DOI: 10.1179/0093469014z.00000000094
|View full text |Cite
|
Sign up to set email alerts
|

Ancient urban life at the Early Horizon center of Caylán, Peru

Abstract: This article examines the development of urban forms of community organization on the north-central coast of Peru during the 1st millennium B.C. Recent mapping and excavations at the Early Horizon center of Caylá n, in the Nepeñ a Valley, provide insights into the nucleation of human groups at an extensive valley floor complex. The results indicate the establishment of an urban core around cross-cutting avenues, while architectural data point towards the existence of multi-functional residential stone-and-mud … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…We note, too, that the SPD decline is not statistically significant; it may also, as cautioned earlier, reflect the erosion of final monument stages as much as any density decrease; and there are large north coast EH sites without monumental architecture (e.g. [69]). Higher precision chronological modelling approaches such as Bayesian methods [70] might shed further light on the issue, and therefore we advise that future research continue to investigate relationships between population and ENSO events.…”
Section: The Development Of Political Centralization On the Northern Peru Coastmentioning
confidence: 54%
“…We note, too, that the SPD decline is not statistically significant; it may also, as cautioned earlier, reflect the erosion of final monument stages as much as any density decrease; and there are large north coast EH sites without monumental architecture (e.g. [69]). Higher precision chronological modelling approaches such as Bayesian methods [70] might shed further light on the issue, and therefore we advise that future research continue to investigate relationships between population and ENSO events.…”
Section: The Development Of Political Centralization On the Northern Peru Coastmentioning
confidence: 54%
“…Nepeña is perhaps most famous for the discovery of spectacular painted murals and friezes at the temples of Pañamarca, Punkurí and Cerro Blanco in the 1930s and 1950s (Bonavia ; Tello ) (Figure ). Recently, fieldwork in the valley has brought valuable insights into previously unknown forms of early urban arrangements (Chicoine and Ikehara ). The beginning of the Early Horizon, or local Nepeña phase (800–450 BCE ) (Table ), marked the emergence of dense human clusters, especially on the valley margins.…”
Section: Urbanization Processes In Early Horizon Nepeñamentioning
confidence: 99%
“…They confirmed that most structures belong to an intense occupation during the Early Horizon. It is currently radiocarbon dated to 800–1 cal BCE (2σ), with most dates clustering between 410 and 200 cal BCE (2σ) (Chicoine and Ikehara , 348). The ruins were later reoccupied as cemeteries, especially during the Late Intermediate period (1000–1470 CE) by groups residing in the adjacent Pan de Azúcar Complex (PV31‐29).…”
Section: Archaeological Research At Caylánmentioning
confidence: 99%
See 2 more Smart Citations